(untitled) (Revista Iberoamericana de Bioética, 2021)
In agriculture it is necessary to take decisions that are closely linked to caring for the environment and protecting the people involved in its management or the communities that are indirectly dependent on it. In this work we will discuss the consequences of using herbicides with glyphosate and assess the implications of their use. Later we will offer the reader considerations from an Ethics of Responsibility that must govern the relationship between man and nature, introducing a change in the contemporary economic model towards an anthropological-environmental paradigm, one that is capable of serving all the interests of man as well as seeking authentic processes for sustainable development.